An Exploration of Job Demands, Job Control, Stress, and Attitudes in Public, Nonprofit, and For-Profit Employees. (December 2014) - Hamann, Darla J.; Foster, Nicole T.
Drawing on the Job Demands-Control-Support model, we argue that job demands, job control, social support, stress, and employee attitudes differ by ownership sector. Using Random Coefficient/ Hierarchical Linear Modeling, we analyze employee perceptions and attitudes from over 900 employees in for-profit, nonprofit, and public nursing homes. We find that nonprofit employees report higher workloads than their for-profit counterparts, and nonprofit and public employees report higher stress levels than their for-profit counterparts. Overall, few sectoral differences were detected in employee decision-making control, social support, or job satisfaction.